Analisis Life Skill Atlet Petanque Kabupaten Musi Rawas dan Upaya Pengembangannya Melalui Strategi Psikologis - Adika Fatahilah; Aditya Trinanda; Syabawaihi (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
The purpose of this study is to analyze the life skills condition of Petanque athletes in Musi Rawas Regency and to identify aspects that require development through psychological strategies, particularly feedback and reinforcement. The method used in this study is a descriptive quantitative approach supported by qualitative data from interviews, involving 35 active Petanque athletes registered under the FOPI Musi Rawas Regency training program. The main instrument used was the Life Skill Inventory questionnaire, covering multiple dimensions, and the data were analyzed descriptively using means and percentages, complemented by qualitative interpretation. The results show that the overall level of athletes’ life skills is in the moderate category (67.3%), with goal setting and time management dimensions categorized as high, while emotional skill and leadership are relatively low. In addition, the lack of positive feedback and structured reinforcement from coaches was identified as a contributing factor to the weak development of athletes’ psychological aspects. In conclusion, psychological strategies through the application of feedback and reinforcement are recommended as effective approaches to improve athletes’ motivation, discipline, and social skills, and can serve as a foundation for developing psychology-based sports training programs at the regional level.   Keywords: Petanque Athletes, Feedback, Life Skills, Reinforcement, Psychological Strategies